Relative concentration of pepper veinal mottle virus in resistant and susceptible chilli plants - Ibrahim, Saleha; Soh, A. C.; Yap, T. C. (Faculty of Agriculture, University of Malaya, 1976)
The multiplication of pepper veinal mottle virus (PVMV) in both resistant and susceptible chilli (Capsicum annunm L.) seemed to follow a cyclical pattern with a maximum peak concentration occurring at 14 days after inoculation. At each period of time, the virus concentration in susceptible plants was distinctly higher than in resistant plants, indicating that the resistance operates by partial suppression of virus multiplication.